Bio-Fertilizers in the Technology of Sunflower Cultivation - Кохан, А. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The using of various kinds of fertilizers has different impact on crop productivity. The increased interest to biological arable farming has induced us to make investigations concerning the influence of various bio-fertilizers on the colonization of sunflower rhizosphere with microorganisms; the dynamics of their number; and correspondingly; their influence on sunflower productivity. As a result of research it has been determined that the seasonal dynamics of the number of epiphytic microorganisms of sunflower rhizosphere different taxonomic units in the gradient of using biofertilizers which have been studied is manifested differently. More intensive development of the fungal flora of sunflower rhizoplane during the periods of pre-sowing and before blossoming has been found in the variant of using Baikal EM-1. The largest number of ammonization bacteria during the vegetation was noticed on the plots where mineral fertilizers and Diazophyt had been used. Agrovit-cor and Baikal EM-1 almost did not influence the quantitative indices. It has been established that the greatest impact on the formation of sunflower harvest among the considered microorganisms had ammonization bacteria; filamentous fungi; and those which decompose organic substances. Thus; as to the complex of indices of microbiological state; soil nutrient regime; and also the indices of sunflower productivity; the variant with the using of micro-biological fertilizer Baikal EM-1 can be recommended to the production with aim of increasing sunflower productivity and maintaining soil fertility.